2017
DOI: 10.1093/geront/gnx101
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Seniors’ Health With Home Care Aides: A Pilot

Abstract: Building PA into the everyday care of older adults and the routine work of HCAs is feasible. The intervention has the potential for further implementation and dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Our project also sought to enhance HCAs′ capacities to promote health and safety for themselves, their clients and their communities. In fact, this program delivered by HCAs led to improvement in their clients’ function measured subjectively and objectively (i.e., fitness tests), as reported elsewhere [26]. This supplementary finding demonstrates our study’s additional impact for the beneficial role of HCAs.…”
Section: Discussionsupporting
confidence: 82%
“…Our project also sought to enhance HCAs′ capacities to promote health and safety for themselves, their clients and their communities. In fact, this program delivered by HCAs led to improvement in their clients’ function measured subjectively and objectively (i.e., fitness tests), as reported elsewhere [26]. This supplementary finding demonstrates our study’s additional impact for the beneficial role of HCAs.…”
Section: Discussionsupporting
confidence: 82%
“…Nine studies (32%) identified use of UCPs in specialty roles, including palliative care, rehabilitation and caring for patients on home ventilation (Giosa, Holyoke, Bender, Tudge, & Gifford, 2015;Guay, Dubois, & Desrosiers, 2014;Herber & Johnston, 2013;Ingleton, Chatwin, Seymour, & Payne, 2011;Johnson, Myers, Scholey, Cyarto, & Ecclestone, 2003;Muramatsu et al, 2017;Pierratos et al, 2017;Royackers et al, 2016;Swedberg et al, 2015). A literature review examining palliative and end-of-life care provided by UCPs in the community identified five key domains of care provided by UCPs: personal care, emotional support, domestic support, respite care and collaborating with professional and family carers (Herber & Johnston, 2013).…”
Section: Specialty Rolesmentioning
confidence: 99%
“…Both studies provided evidence to support the development of UCP skills to provide rehabilitation services to patients in the community. Other studies examined more independent roles for UCPs in improving the functional status of patients (Johnson et al, 2003;Muramatsu et al, 2017). These roles included the delivery of interventions including a home exercise programme (Johnson et al, 2003) and health promotion intervention, which focused on increasing physical activity in seniors (Muramatsu et al, 2017).…”
Section: Specialty Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published American study explored the ability of home care aides (may be considered equivalent to support workers in Australia) to increase the physical activity levels of frail older people accessing community care services through the use of chair-based activities and motivational techniques and found them to be effective. 15 …”
Section: Introductionmentioning
confidence: 99%